Pengaruh Strategi Pembelajaran Predict, Observe, and Explain (POE) dalam Model Discovery Learning terhadap Motivasi dan Hasil Belajar Peserta Didik Kelas XI MAN 1 Barru - Nasution, Sitti Hajar; Sugiarti, Sugiarti; Auliah, Army (Chemistry Education Review (CER), 2024)
This study is an experimental research that aims to examine the influence of Predict, Observe, and Explain (POE) learning strategies in the Discovery learning model on the students’ learning motivation and learning outcomes. The research design used was the Posttest-Only Control Design. The population of the study was all students of grade XI MIPA at MAN 1 Barru. The samples were students in grade XI MIPA 1 as the experimental class and grade XI MIPA 2 as the control class. The data analysis techniques used were descriptive and inferential statistical analysis. The results of the study reveal that learning using the Predict, Observe, and Explain (POE) strategy in the Discovery learning model obtain a value of 78% learning motivation, 78% cognitive learning outcomes, 84% affective learning outcomes, and 82% higher skills learning outcomes compared to learning in the control class, so it has significant effect based on hypothesis testing of learning motivation data and learning outcomes with a Sig value. (1-tailed) < 0.05. In addition, learning motivation has a correlation with learning outcomes with Pearson correlation values of 0.824, 0.853, and 0.75. These values indicate that learning motivation has a correlation with learning outcomes at a very high and faily high level of closeness. Therefore, the conclusion of the study is the use of Predict, Observe, and Explain (POE) strategy in the Discovery learning model affects the students’ learning motivation and learning outcomes.